People and wild plants - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2001)
Applied Ethnobotany: People, Wild Plant Use and Conservation By A B Cunningham, Earthscan, 2000. 300 pp. ISBN 1853836974 GBP 24.95 Euro 40.50